Abnormality in field physical test predicts a reduced quadriceps strength in patients with hip- or knee-osteoarthritis. A prospective observational study. - Quentin Fanget; Anargyros Verdilos; Samuel Adelou; Vivien Reynaud; Stéphane Boisgard; Stéphane Descamps; Bruno Pereira; Ruddy Richard; Emmanuel Coudeyre; Frédéric Costes (PLoS ONE)
Background In osteoarthritis quadriceps strength is an important outcome to assess exercise capacity and recovery after arthroplasty. However, its measurement is limited due to lack of time and the need for trained personnel and equipment whose accuracy is verified. Objectives To find out the determinants of a reduced quadriceps strength and to establish a score to screen for it. Methods In an observational prospective study, we evaluated patients presenting with an unilateral knee (KOA) or a hip (HOA) osteoarthritis before a scheduled arthroplasty. We measured body composition, exercise capacity, muscle strength, balance, WOMAC score, quality of life and physical activity. Isometric maximal voluntary quadriceps force (MVCq) was determined on both lower limbs and a reduced strength was retained when at least one measurement was lower than 1 standard deviation of normal value. Results We included 376 patients, 247 (66%) with KOA and 129 (34%) with HOA. Their mean age was 67±8 years, and mean BMI 31.4±6.9 kg/m2. MVCq was reduced in 217 (58%). Compared those with a preserved MVCq, these patients had a significant higher BMI and lean mass, a sex ratio (more men), an altered field physical tests and WOMAC score. The best logistic regression model for a decreased quadriceps force included pathology, age, sex, BMI, five sit to stand test (FTSST) and maximal gait speed (AUC was 0.87 [95%CI 0.83-0.90]). We developed a predictive equation for a reduced MVCq as follows: Y = 1/1+ exp[-(-0.051*age -1.25*max gait speed + 0.09*FTSST + 0.16*BMI + 1.1 (for KOA) + 2.41 (for male) -1.79]. Conclusion MVCq is reduced with a high prevalence on patients with KOA or HOA. A low performance in one the selected field physical test associated with age and BMI allows to screen for those in whom a measurement of MVCq could be of interest before arthroplasty.